Ectropion Prevention In Lower Blepharoplasty With Abnormal Distraction Test And Snap Back Test - Nainggolan, Kartika Sari; Mahardika Venansius Purba, Agung (Publikasi Indonesia, 2025)
Ectropion is a malposition of the eyelid in which the lower eyelid falls away from its normal position to the globe with exposure of the palpebral and bulbar conjunctiva.1 Ectropion is the most common serious complication following lower blepharoplasty for the correction of baggy eyelid.2 Although lower blepharoplasty may be considered one of the most gratifying plastic surgery, but if ectropion occurs, it will be very distressing to both patient and surgeon. This case report, we describe about our patients, between April 2023 to June 2025 of all 68 our patients who underwent Lower Blepharoplasty, in the early year before we implemented preventive techniques, we found 2 patients who had ectropion. We corrected those 2 patients with Lateral Tarsal Strip. Our patients who underwent Lower Blepharoplasty with doubtful to abnormal snap back and distraction test results and we performed the preventive technique. After that, we no longer found cases of ectropion in our patients.